The effect of age and culture on brand loyalty in the South African motor industry - Hempel, Martin Johan (Rhodes University, Faculty of Commerce, Rhodes Business School, 2019)
It has become imperative for companies in the motor industry to study and understand the notion of brand loyalty due to the many inherent advantages that it offers. Although existing literature provides extensive information on brand loyalty, the concept of brand loyalty is not constant across all industries. Factors such as age and culture also alter the effects of brand loyalty and the degree of brand loyalty generated within a consumer. Taking these variables into account, this study sets out to establish if age and culture have an effect on brand loyalty in the South African motor industry. The method in which motor companies emit marketing signals are also explored to establish if the emitted marketing signals are able to assist in the generation of brand loyalty. A South African real estate agent group agreed to participate in the research and became the sample population for the study. 190 successfully completed questionnaires were obtained in the data collection process and data with a Cronbach Alpha Coefficient (Î±) of 0.7662 proved that the data had satisfactory reliability. The data was processed and analysed in the statistical analysis program Stata. The study discovered that marketing signals don't assist in the generation of brand loyalty in the South African motor industry. It is suggested that it is more plausible that marketing signals can assist to maintain brand loyalty, rather than to generate brand loyalty. The study also discovered that culture does not have an effect on brand loyalty in the South African motor industry. However, after considering that the cultural distribution of the sample was significantly skewed, the sample is regarded as an unreliable test of the effect of culture on brand loyalty. The study also discovered that age doesn't have an effect brand loyalty in the South African motor industry. The researcher noted that the previously cognitively strenuous process of obtaining information has become more simplified by the internet and could potentially have reduced the generating of brand loyalty among older consumers. A final test was conducted to ascertain if relationships exist between the four stages of loyalty. The study suggested that all four loyalty stages are connected which confirms that brand loyalty is generated by both attitudinal and behavioural dimensions.
Keywords: Brand loyalty -- South Africa; Automobile industry and trade -- South Africa; Consumer satisfaction -- South Africa; Consumer behavior -- South Africa; Older consumers -- South Africa; Consumers -- South Africa -- Cross-cultural studies